2011
DOI: 10.1089/zeb.2010.0680
|View full text |Cite
|
Sign up to set email alerts
|

Observation ofmiRNAGene Expression in Zebrafish Embryos byIn SituHybridization to MicroRNA Primary Transcripts

Abstract: MicroRNAs (miRNAs) add a previously unexpected layer to the post-transcriptional regulation of protein production. Although locked nucleic acids (LNAs) reveal the distribution of mature miRNAs by in situ hybridization (ISH) experiments in zebrafish and other organisms, high cost has restricted their use. Further, LNA probes designed to recognize mature miRNAs do not distinguish expression patterns of two miRNA genes that produce the same mature miRNA sequence. Riboprobes are substantially less expensive than L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 58 publications
0
30
0
Order By: Relevance
“…Given that previous findings have shown a high level of miR-199a-5p expression in the developing mouse and zebrafish mesodermal tissues, it is probable that miR-199a-5p has important myogenic and non-myogenic roles in early embryonic development. 20,31 Using miRNA target prediction programs such as TargetScan, MicroCosm, and miRDB, with an emphasis on those targets whose miR-199a-5p-binding sites were evolutionarily conserved and had been defined as having a functional role in muscle, several members of the WNT signaling pathway were identified as predicted downstream targets (Figure 7a and Supplementary Figure S2). Previous work had identified several hypoxia-regulated mRNAs, such as HIF1a and SIRT1, as being direct miR-199a-5p targets in cardiomyocytes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that previous findings have shown a high level of miR-199a-5p expression in the developing mouse and zebrafish mesodermal tissues, it is probable that miR-199a-5p has important myogenic and non-myogenic roles in early embryonic development. 20,31 Using miRNA target prediction programs such as TargetScan, MicroCosm, and miRDB, with an emphasis on those targets whose miR-199a-5p-binding sites were evolutionarily conserved and had been defined as having a functional role in muscle, several members of the WNT signaling pathway were identified as predicted downstream targets (Figure 7a and Supplementary Figure S2). Previous work had identified several hypoxia-regulated mRNAs, such as HIF1a and SIRT1, as being direct miR-199a-5p targets in cardiomyocytes.…”
Section: Resultsmentioning
confidence: 99%
“…As previous findings have shown a high level of expression of miR-199a-5p in developing zebrafish and mouse mesodermal tissues, it is likely that miR-199a-5p has important non-myogenic roles in early development. 20,31 Genomic removal of both the miR-199a-1 and miR-199a-2 transcripts along with a miR-199a-1/miR-199a-2 compound deletion in mice may elucidate functional roles of each miR-199a-5p transcript. Further characterization of miR199a-5p under different pathogenic conditions might elucidate its function as a regulator of other non-WNT signaling targets.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, we found that during DLAV plexus morphogenesis the effects of circulatory flow and VEGFR signaling are generally additive, consistent with two models. The first and most likely possibility (see Lawson et al, 2001;Wienholds et al, 2005;Covassin et al, 2006;Parmar et al, 2006;Choi et al, 2007;Siekmann and Lawson, 2007;Hogan et al, 2009b;North et al, 2009;He et al, 2011;Wang et al, 2011) is that circulatory flow promotes, but is not absolutely required, for VEGF signaling during DLAV plexus morphogenesis (Fig. 4I).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, klf2a expression in the trunk vasculature is circulation dependent. Taken together, these observations suggest that circulatory flow and VEGF signaling might be functionally related in the context of DLAV plexus morphogenesis, as they are during aortic arch angiogenesis (Lawson et al, 2001;Wienholds et al, 2005;Covassin et al, 2006;Parmar et al, 2006;Choi et al, 2007;Siekmann and Lawson, 2007;Hogan et al, 2009b;North et al, 2009;He et al, 2011;Wang et al, 2011).…”
Section: Characterization Of Circulatory Flow During Dlav Plexus Morpmentioning
confidence: 96%
“…Therefore, non-radioactive-labeled synthetic RNA oligonucleotide probes, such as 2-O-methyl RNA oligonucleotides, and locked nucleic acids (LNA) are currently used since they can overcome this problem, allowing an overall enhancing of the probe signal [6,63]. To distinguish between genes that encode the same mature miRNA sequence, Postlethwait and collaborators [64] developed the use of digoxigenin-labeled riboprobes designed to bind to miRNA primary transcripts, allowing the observation of miRNA expression for both intergenic and intronic miRNAs. Alternatively to ISH, zebrafish microRNA expression patterns have also been investigated by qPCR, microarray, RNA-seq, and Northern blot analyses at different developmental stages and in different tissues [55,59,65].…”
Section: Mirna Expression Analysesmentioning
confidence: 99%